Pengaruh Social Media Marketing melalui Instagram terhadap Brand Awareness Muarchee Penang - Heftina Simbolon; Binsar Sihombing; Muhammad Roestian Fahmi Nasution; Elvina Emanuella Br Surbakti (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
The expansion of micro, small, and medium enterprises (MSMEs) within Indonesia’s food and beverage industry has shown rapid progress; nevertheless, many entrepreneurs continue to encounter difficulties in enhancing brand awareness due to the limited optimization of digital marketing efforts. This research investigates the influence of Instagram-based social media marketing on the brand awareness of Muarchee Penang by applying the 4C framework, which encompasses context, communication, collaboration, and connection. The study adopts a quantitative methodology with a causal associative design and involves 100 followers of the Muarchee Penang Instagram account selected through purposive sampling. Data were gathered using structured questionnaires and processed through multiple linear regression analysis. The results reveal that context and communication significantly and positively affect brand awareness, whereas collaboration and connection do not demonstrate a significant impact. However, when assessed collectively, the four variables exhibit a positive and significant influence, explaining 43 percent of the variation in brand awareness. Overall, the development of brand awareness on Instagram is driven more by content relevance, consistency, and the effectiveness of two-way communication than by posting frequency or poorly directed collaborations. Accordingly, Muarchee Penang is advised to consistently showcase visually appealing content to reinforce its brand image, convey informative messages emphasizing product benefits and customer testimonials, maintain consistent visual identity elements such as colors and logos across posts, actively interact with its audience, and pursue collaborations and customer engagement initiatives that align with the brand’s identity.